The Wahhabi Movement and Abdul Aziz Al-Saud in the Formation of the Third Period Saudi Dynasty (Emirate of Riyadh 1901-1932 AD) - Ridwan; Samsul Bahri Hasibuan; Usman Supendi; Ajid Thohir (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to explain the Wahhabiyah movement and Abdul Aziz al-Saud in the process of forming the third period of the Saudi dynasty after the collapse of the first and second periods. The method used is a historical method consisting of heuristics, criticism, interpretation and historiography. The sources used include a book entitled the Book of At-Tauhid, written by Muhammad bin Abdul Wahhab, a book entitled Imam Muhammad bin Abdul Wahhab Da'wah and Traces of His Struggle, written by Abdul Aziz bin Abdullah bin Baz and other books. The result of the discussion in this article is that Abdul Aziz al-Saud or usually called Ibnu Saud was the founder of the third Saudi Dynasty, after the second Saudi Dynasty collapsed and was defeated by the Ar-Rashid Clan, in 1901 AD. Al-Saud, who allied with As-Shabah, which was supported by Britain, succeeded in defeating the Rashid Clan so that Abdul Aziz succeeded in capturing the city of Riyadh. The conquest of other cities continued by forming an Ikhwani military unit with a Wahhabi ideology. The entire area of ​​Najd and its surroundings was successfully captured by Abdul Aziz and his troops, as well as the 'Asir area, then the Hijaz region and succeeded in defeating Syarif Husein, areas around the Hijaz such as Jeddah, Tha 'if, Mecca and Medina were successfully captured, so that Abdul Aziz became the ruler of the Hijaz and Najd and then he announced the unification or unification of their various territories under the name of the Kingdom of Saudi Arabia (Kingdom of Saudi Arabia) on September 22 1932 AD, thus ending the third Saudi Dynasty.